PENGARUH PROFITABILITAS, CORPORATE GOVERNANCE DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE - Wila, Novelia H. R. Here; Ga, Linda Lomi; Pau, Sarlin P. Nawa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to examine the effect of profitability, corporate governance consisting of institutional ownership, independent commissioner and financial distress on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sample in this study is a manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Sample selection in this study using purposive sampling method and obtained 37 companies. Data analysis wa carried out using panel data regression model and using Eviews version 12 software. The result of this study indicate that profitability had effect on tax avoidance, institutional ownership had effect on taxavoidance, independent commissioner has no effect on tax avoidance, financial distress has no effect on tax avoidance, and profitability, institutional ownership, independent commissioner and financial distress have a simultaneous effect on tax avoidance.